(untitled) (Bangladesh Medical Journal, 2019)
Children mostly suffer from respiratory illnesses around the world. Situation is not different in Bangladesh as suggested by many studies on childhood illness. But most of these studies have been done in tertiary level hospitals located in urban areas and very few were done in rural setting. This study was conducted to estimate the frequency and to determine the pattern of respiratory morbidity among children and also to assess the impact of passive smoking on the magnitude of acute respiratory tract infections (ARI) among children. This was an observational study. It was carried out on 1002 children over a period of about 180 days, who attended the Tungipara Upazila Health Complex (UHC), Gopalganj, Bangladesh between January 2018 and June 2018. Data were collected through face to face interview, physical examination, relevant investigations and collected data in the questionnaire for respiratory illness and others then respiratory data were not collected. Out of 1002 children, more then half (54%) were male and the age range was new born to 168 months. Among them upper respiratory tract infections (URTI) were 98.5% as against only 1.5% of lower respiratory tract infections (LRTI). In this study, 38% fathers were smoker and no mother found as smoker. Families of 63% patients used smoke producing substances for cooking. Respiratory illness was more prevalent among the children whose fathers used to smoke tobacco χ2 (1) 380 P 0.01. As well as babies more vulnerable for respiratory morbidity where smoke producing fuel used for cooking χ2 (1) 170 P 0.01. Children suffered more from diseases affecting the respiratory system than diseases of other systems. Simple cough related illness was the most common URTI. Under 05 children suffered most. Respiratory illness was more common among those whose fathers smoked tobacco. Children were more vulnerable to respiratory morbidity, where smoke producing fuel used for cooking. There need multicentric study to observe the real picture of respiratory morbidity. Bangladesh Med J. 2019 Jan; 48 (1): 1-4